Effects of repeated cranial electrotherapy stimulation on physiological and behavioral responses to acute stress: a double-blind randomized clinical trial - Okano, Kana; Lee, Marissa Marko; Hart-Pomerantz, Hannah; Smith, Marisa; Sandone, Madelyn K.; Harvey, Travis; Brunyé, Tad T. (Frontiers in Human Neuroscience, 2025)
BackgroundCranial electrotherapy stimulation (CES) is a low-intensity, pulsed neuromodulation technique widely marketed for reducing stress and anxiety. Despite its popularity, empirical evidence for its efficacy remains mixed, with few studies employing rigorous controls, standardized protocols, and repeated CES exposures.ObjectiveTo evaluate whether repeated CES sessions can attenuate physiological, biochemical, cognitive, and affective responses to an acute laboratory stressor.MethodsA double-blind, randomized, placebo-controlled clinical trial was conducted with 46 healthy participants (27 military personnel, 19 civilians). Participants were randomized to receive either active CES (250–500 μA at 0.5Hz, individualized intensity) or sham stimulation for 20 sessions over approximately four weeks. At baseline and follow-up visits, participants underwent acute stress induction using torso shock; measures included physiological (heart rate, heart rate variability, respiration rate, pupil diameter), biochemical (salivary alpha-amylase, cortisol), cognitive (spatial orientation, recognition memory, decision-making), and affective (State-Trait Anxiety Inventory) indices.ResultsStress induction reliably elevated sympathetic-adrenal medulla (SAM) and hypothalamic-pituitary-adrenal (HPA) markers as well as subjective anxiety. However, across nearly all outcomes, active CES did not differ significantly from sham, nor were there interactions with session (baseline vs. follow-up). No meaningful group differences were observed in stress recovery, self-reported anxiety, or stress-related cognitive performance.ConclusionsThese predominantly null findings challenge prevailing mechanistic accounts of CES and suggest limited efficacy in buffering acute stress responses in healthy, neurotypical individuals. Further controlled trials are needed to explore alternative parameters, populations, and neurophysiological endpoints to better understand CES’s therapeutic potential.Clinical trial registrationhttps://clinicaltrials.gov/, identifier NCT06034496.